PENERAPAN ASAS DOMINUS LITIS DALAM HUKUM POSITIF DI INDONESIA SETELAH DISAHKANNYA KUHAP BARU - Lalu Panca Tresna D; Muhammad Rifaldi Setiawan (The Juris, 2025)
Prosecutors are central figures in the administration of criminal justice because they have the authority to determine cases (dominus litis) to be forwarded to the courts. However, in fact, the application of the Dominus Litis principle is not optimal, such as the implementation of horizontal supervision and the termination of cases. examines the application of the principle of dominus litis to positit law in Indonesia. Normative legal research with the Approach of the Act; futuristic and comparative. The application of the Dominus litis Principle in the Criminal Procedure Code is contained in Article 1 Number (6) letters a and b; 139, as the principle of functional differentiation in Articles 14 and 137, based on the position and function of the prosecutor in the criminal justice system is regulated in Article 140 paragraph (2); Law No. 11 of 2021 Amendment to Law No. 16 of 2004 and Constitutional Court Decision No. 55/PUU-XI/2013 and No. 29/PUU-XIV/2016. New KUHAP. Prosecutors in Indonesia are in the Executive Institution, have several principles, do not have investigative authority; the scope of criminal, civil and administrative prosecutions of the State and not being double nature of the prosecutors and the macau in the Judiciary, focused on the principle of legality, has the authority to investigate, prosecute criminal and civil prosecutors and is double nature of the prosecutors.